Microglia and Astrocyte Function and Communication: What Do We Know in Humans? - Garland, Emma F.; Hartnell, Iain J.; Boche, Delphine (Frontiers in Neuroscience, 2022)
Microglia and astrocytes play essential roles in the central nervous system contributing to many functions including homeostasis, immune response, blood-brain barrier maintenance and synaptic support. Evidence has emerged from experimental models of communication between these cells, influencing each other and coordinating their effects on the brain environment. However, due to the difference in glial cells between humans and rodents, it is essential to confirm the relevance of these findings in human brains. Here, we aim to review the current knowledge on microglia-astrocyte crosstalk in humans, exploring novel methodological techniques used in health and disease conditions. This will include an in-depth look at cell culture and iPSCs, post-mortem studies, imaging and fluid biomarkers, genetics and transcriptomic data. In this review, we will discuss the advantages and limitations of these methods, highlighting the understanding these methods have brought the field on these cell communicative abilities, and the knowledge gaps that remain.